ISOLATION, CHARACTERIZATION AND SCALE-UP OF FOETAL AMNIOTIC MEMBRANE DERIVED MULTIPOTENT STROMAL CELLS FOR THERAPEUTIC APPLICATIONS - JAIANAND KANNAIYAN; BALAJI PAULRAJ (International Journal of Pharma and Bio Sciences, 2015)
Stem cells are the future frontier in curing diseases and preventing ailments. Recent studies have shown that Multipotent Stromal Cells are promising candidates for stem cell therapy and regenerative medicine. Amniotic membrane is a good source of MSCs and potentially be used for regenerative medicine. However, the use of MSCs for therapeutic application is based on their subsequent large-scale in-vitro expansion. A fast and efficient protocol for generation of large quantities of MSCs is required to meet the clinical demand and biomedical research needs. In the present study, we successfully isolated, characterized and up-scaled up to P2 to get as many as 5.57x109 cells from a single placenta and also observed up to P10 with no significant change in viability, stemness and karyotyping. To confirm differentiation potential, a multi-lineage differentiation assay was conducted for their exploitation and proliferation was measured based on CPDL. Immuno-phenotyping showed that major population was of mesenchymal origin. We concluded that AM-MSCs is a promising candidate for stem cell therapy.